Creative Traditions and Ecology of Heritage - Vintilă Mihăilescu (Martor, 2017)
Eric Hobsbawm used a distinction between “customs” (collective representations of the past experienced as present) and “tradition” (as “imagined past”, a product of modernity), while at the same time introducing the concept of “invented traditions” into the theoretical terminology of the social sciences. He thus opened the way for a nuanced analysis of the concepts that come into discussion in the analysis of the relation between the past and the present that re-uses it. Starting from this methodological distinction, the article presents a discussion of past and present by analysing such concepts as tradition, patrimony, legacy, succession, and preservation. These are the concepts that govern the relation between and regarding the cultural-identitary politics that correspond to them, and this can be richly exemplified in the case of Romania.